Human 3D Gastrointestinal Microtissue Barrier Function As a Predictor of Drug-Induced Diarrhea. (26th October 2018) - Peters, Matthew F; Landry, Tim; Pin, Carmen; Maratea, Kim; Dick, Cortni; Wagoner, Matthew P; Choy, Allison L; Barthlow, Herb; Snow, Deb; Stevens, Zachary; Armento, Alex; Scott, Clay W; et al.
Abstract: Drug-induced gastrointestinal toxicities (GITs) rank among the most common clinical side effects. Preclinical efforts to reduce incidence are limited by inadequate predictivity of in vitro assays. Recent breakthroughs in in vitro culture methods support intestinal stem cell maintenance and continual differentiation into the epithelial cell types resident in the intestine. These diverse cells self-assemble into microtissues with in vivo -like architecture. Here, we evaluate human GI microtissues grown in transwell plates that allow apical and/or basolateral drug treatment and 96-well throughput. Evaluation of assay utility focused on predictivity for diarrhea because this adverse effect correlates with intestinal barrier dysfunction which can be measured in GI microtissues using transepithelial electrical resistance (TEER). A validation set of widely prescribed drugs was assembled and tested for effects on TEER. When the resulting TEER inhibition potencies were adjusted for clinical exposure, a threshold was identified that distinguished drugs that induced clinical diarrhea from those that lack this liability. Microtissue TEER assay predictivity was further challenged with a smaller set of drugs whose clinical development was limited by diarrhea that was unexpected based on 1-month animal studies. Microtissue TEER accurately predicted diarrhea for each of these drugs. The label-free nature of TEER enabled repeated quantitation with sufficient precision to develop a mathematical model describing the temporal dynamics of barrier damage and recovery. This human 3D GI microtissue is the first in vitro assay with validated predictivity for diarrhea-inducing drugs. It should provide a platform for lead optimization and offers potential for dose schedule exploration.